Salivary excretion of systemically injected [18F]DCFPyL in prostate cancer patients undergoing PSMA scans - Fernandes, Bruna; Roy, Jyoti; Basuli, Falguni; Warner, Blake M.; Lindenberg, Liza; Mena, Esther; Adler, Steven S.; Griffiths, Gary L.; Choyke, Peter L.; Lin, Frank I. (Frontiers in Oncology, 2024)
Introduction: Prostate-specific membrane antigen (PSMA) is present in high amounts in salivary glands, but it is unclear whether labeled binders of PSMA are excreted in the saliva. Methods: Ten patients with prostate cancer underwent whole-body [ 18 F]DCFPyL PET/CT (NCT03181867), and saliva samples were collected between 0-120 minutes post-injection. [ 18 F]DCFPyL salivary excretion was measured over 120 minutes and expressed as %ID/g. Protein-associated binding was estimated by the percentage of [ 18 F]DCFPyL versus parent radiotracer. Results: All PET scans of 10 patients (69±8 years) with histologically confirmed prostate cancer (PSA= 2.4±2.4, and Gleason Grade = 6-9) showed high uptake of [ 18 F]-DCFPyL in salivary glands while 8 patients demonstrated high uptake in the saliva at 45 minutes. The intact [ 18 F]-DCFPyL (98%) was also confirmed in the saliva samples at 120 min with increasing salivary radioactivity between 30-120 min. Conclusion: Systemically injected [ 18 F]DCFPyL shows salivary gland uptake, an increasing amount of which is secreted in saliva over time and is not maximized by 120 minutes post-injection. Although probably insignificant for diagnostic studies, patients undergoing PSMA-targeted therapies should be aware of radioactivity in saliva.